(untitled) (Nordic Journal of African Studies, 2009)
This paper examines The High Tone Syllable (HTS) in Central Yorùbá dialects: Èkìtì, Ifẹ̀, Ìjẹ̀sà and Mọ̀bà dialects. The High Tone Syllable occurs between the subject and the verb in Central Yoruba dialects. This paper shows that the HTS usually gets deleted in Ekiti dialects. However, in Ifẹ̀, Ijẹ̀sà and Mọ̀bà dialects the HTS regularly assimilates the form of the vowel of the last syllable of the preceding subject NP whenever the NP shows up. The paper also justifies the claim that the position vacated by focused subject NP is always left empty. Hence what is regarded as pronominal substitute in Yoruba is actually an occurrence of the HTS.